PKM Kewirausahaan Diversifikasi Produk Dadar Gulung Menjadi Mini Crepe Roll - Mitha Evalista; Irfan Yunus; Mohamad Ikbal Riski A. Danial; Fitrah Widya Wati; Mas’ud Uqbah Al Ansyari (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Traditional food is known as market snacks because in the past these snacks were found in many traditional markets. In this modern era, some people consider that omelette rolls are an outdated traditional food or snack. The popularity of rolled omelets is increasingly eroded by modern snacks that are more contemporary and practical. This causes a lack of public interest in omelette rolls, especially the younger generation. This condition is feared to cause the rolled omelette, which is a traditional Indonesian culinary richness, to be forgotten in the future. Therefore, a diversification process must be carried out so that the rolled omelet remains in the market. The process of diversifying omelette rolls as a traditional food into a modern product, namely "Mini Crepe Roll" is a strategic step to maintain its existence and popularity in the midst of a more contemporary and practical onslaught of modern snacks. This Mini Crepe Roll product is an introductory food or dessert that is suitable to eat for Indonesian snack fans. Besides that, this food does not use harmful preservatives and is safe to consume. To attract customer interest, Mini Crepe Roll food products are packaged and served attractively, practically, and ready to eat. In this activity, not only focus on the mini crepe roll production process, but also on business and marketing aspects This is so that mini crepe roll products can be well received by consumers and have competitiveness in the market.